Two-Tier Workplace Compensation: Issues and Remedies - MacNeil, Michael (Canadian Labour and Employment Law Journal, 2013)
As a result of the recession that began in 2008, many employers are look- ing for ways to cut labour costs. One way of doing so is to impose two-tier compensation schemes, whereby younger employees do essentially the same job as older ones, but for lower wages and benefits. The key concern of this paper is how Canadian labour, employment and human rights law could respond to the differential impact of two-tier schemes on younger workers. First, the author reviews the use of two-tier systems in the United States and Canada, showing that they affect not only workers' wages and benefits but also their pensions, as employers move from defined benefit to defined contribution plans. In the next part of the paper, he analyses arbitral, labour board and human rights tribunal case law, arguing that lower-tier workers face significant barriers in seeking legal recourse through duty of fair representation or human rights complaints. The author concludes with an overview of the restrictions on two-tier schemes in the Quebec employment standards statute, and discusses the difficulties of enacting similar legislation in other Canadian jurisdictions.